Morphological and genetic characterization and the nationwide distribution of the phototrophic dinoflagellate Scrippsiella lachrymosa in the Korean waters - Lee, Sung Yeon; Jeong, Hae Jin; You, Ji Hyun; Kim, So Jin (Algae (Korean Phycological Society), 2018)
The phototrophic dinoflagellate genus Scrippsiella is known to have a worldwide distribution. Here, we report for the first time, the occurrence of Scrippsiella lachrymosa in Korean waters. Unlike the other stains of S. lachrymosa whose cultures had been established from cysts in the sediments, the clonal culture of the Korean strain of S. lachrymosa was established from motile cells. When the sulcal plates of S. lachrymosa, which have not been fully described to date, were carefully examined using scanning electron microscopy, the Korean strain of S. lachrymosa clearly exhibited the anterior sulcal plate (s.a.), right sulcal plate (s.d.), leftsulcal plate (s.s.), median sulcal plate (s.m.), and posterior sulcal plate (s.p.). When properly aligned, the large subunit (LSU) rDNA sequence of the Korean strain of S. lachrymosa was ca. 1% different from those of two Norwegian strains of S. lachrymosa, the only strains for which LSU sequences have been reported. The internal transcribed spacer (ITS) rDNA sequence of the Korean strain of S. lachrymosa was also ca. 1% different from those of the Scottish and Chinese strains and 3% different from those of the Canadian, German, Greek, and Portuguese strains. Thus, the Korean S. lachrymosa strain has unique LSU and ITS sequences. The abundances of S. lachrymosa in the waters of 28 stations, located in the East, West, and South Sea of Korea, were quantified in four seasons from January 2016 to October 2017, using quantitative real-time polymerase chain reaction method and newly designed specific primer-probe sets. Its abundances were >0.1 cells mL-1 at eight stations in January and March 2016 and March 2017, and its highest abundance in Korean waters was 26 cells mL-1. Thus, S. lachrymosa has a nationwide distribution in Korean waters as motile cells.